ANALYSIS OF “UZBEK LANGUAGE” TEXTBOOKS IN AFGHANISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article has been read and analyzed the status of native language textbooks. Also, the factors that negatively affect the potential of the native language knowledge of students of the Uzbek nationality in Afghanistan is investigated.